2021
DOI: 10.1364/optica.421257
|View full text |Cite
|
Sign up to set email alerts
|

Modeling nonlinear microscopy near index-mismatched interfaces

Abstract: Nonlinear microscopy is widely used to characterize thick, optically heterogeneous biological samples. While quantitative image analysis requires accurately describing the contrast mechanisms at play, the majority of established numerical models neglect the influence of field distortion caused by sample heterogeneity near focus. In this work, we show experimentally and numerically that finite-difference time-domain (FDTD) methods are applicable to model focused fields interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 43 publications
4
17
0
Order By: Relevance
“…The pTHG response shows predominantly single-peak modulation, which indicates that the sample is composed of concentric crystalline subdomains that form vertical interfaces for THG imaging. The pTHG angle distribution is radial, consistent with the presence of concentric index-mismatched vertical interfaces . Such a concentric structure is in line with a pathogenesis process of the calcification that has been described in different organs including kidney, skin, or breast and attributes these micrometer spherical entities made of calcium phosphate apatite to the agglomeration of nanospherules.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The pTHG response shows predominantly single-peak modulation, which indicates that the sample is composed of concentric crystalline subdomains that form vertical interfaces for THG imaging. The pTHG angle distribution is radial, consistent with the presence of concentric index-mismatched vertical interfaces . Such a concentric structure is in line with a pathogenesis process of the calcification that has been described in different organs including kidney, skin, or breast and attributes these micrometer spherical entities made of calcium phosphate apatite to the agglomeration of nanospherules.…”
Section: Resultssupporting
confidence: 81%
“…This expression corresponds to a characteristic double-peaked profile as shown in Figure b. In the case of pTHG from an interface parallel to the beam propagation, i.e. , when a linearly polarized excitation beam is focused near a vertical discontinuity of the refractive index, the THG process is significantly altered by field distortions , and cannot be easily described analytically. In high-NA microscopy experiments, the signal is often found to follow a polarization dependence in the form TH G V ( ϕ ) A + B 0.25em cos 2 ( ϕ ϕ 0 ) I 3 where A and B are constants.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, the FDTD family of methods calculate the electric fields at every point of a 3D grid in successive times by solving discretized Maxwell equations for specified materials. The implementation details and the validity of FDTD strategies in the context of nonlinear microscopy have been demonstrated (Morizet et al, 2021). Figure 4A shows the schematic of an FDTD simulation for SHG microscopy under circular polarized excitation to a vertical interface.…”
Section: Resultsmentioning
confidence: 99%
“…As a complementary tool with a different principle, the finite-difference time-domain (FDTD) approach has been adopted in many microscopy technique simulations, such as wide-field, confocal, and SHG microscopy (Török et al, 2008;Choi et al, 2007;van der Kolk et al, 2018). More recently, the ubiquitous geometry of a vertical interface between index-mismatched media and the case of polarized THG contrasts are analyzed based on FDTD methods (Morizet et al, 2021). The effects of the refractive index mismatches and the imaging depth on CD-SHG microscopy have not yet been studied.…”
Section: Introductionmentioning
confidence: 99%
“…THG imaging contrast is strongly influenced by wavelength-scale sample heterogeneity, which has been extensively studied 15,[40][41][42][43] . In addition to this dependence on sample microstructure, it has also been shown that biological THG can be enhanced by the presence of strong absorbers such as porphyrin-based pigments.…”
Section: Resonances In Thg Spectramentioning
confidence: 99%